Depletion of Myostatin b Promotes Somatic Growth and Lipid Metabolism in Zebrafish - Gao, Yanping; Dai, Ziru; Shi, Chuang; Zhai, Gang; Jin, Xia; He, Jiangyan; Lou, Qiyong; Yin, Zhan (Frontiers in Endocrinology, 2016)
Myostatin (MSTN) is a negative regulator of myogenesis in vertebrates. Depletion of mstn resulted in elevated muscle growth in several animal species. However, the report on the complete ablation of mstn in teleost fish has not yet become available. In this study, two independent mstnb-deficient mutant lines in zebrafish were generated with the TALENs technique. In the mstnb-deficient zebrafish, enhanced muscle growth with muscle fiber hyperplasia was achieved. Beginning at the adult stage (80 days postfertilization), the mstnb-deficient zebrafish exhibited increased circumferences and body weights compared with the wild-type sibling control fish. Although the overall total lipid/body weight ratios remained similar between the mstnb-deficient zebrafish and the control fish, the distribution of lipids was altered. The size of the visceral adipose tissues became smaller while more lipids accumulated in skeletal muscle in the mstnb-deficient zebrafish than in the wild-type control fish. Based on the transcriptional expression profiles, our results revealed that lipid metabolism, including lipolysis and lipogenesis processes, was highly activated in the mstnb-deficient zebrafish, which indicated the transition of energy metabolism from protein-dependent to lipid-dependent in mstnb-deficient zebrafish. Our mstnb-deficient model could be valuable in understanding not only the growth trait regulation in teleosts but also the mechanisms of teleost energy metabolism.